Porcine circovirus type 2 (PCV2) induces cell proliferation, fusion, and chemokine expression in swine monocytic cells in vitro - Tsai, Yi-Chieh (EDP Sciences, 2010)
Granulomatous lymphadenitis is one of the pathognomonic lesions in post-weaning multisystemic wasting syndrome (PMWS)-affected pigs. This unique lesion has not been reported in direct association with viral infection in pigs. The objective of the present study was to evaluate whether porcine circovirus type 2 (PCV2) alone is able to induce functional modulation in porcine monocytic cells in vitro to elucidate its possible role in the development of granulomatous inflammation. It was found that the proliferation activity of blood monocytes (Mo) and monocyte-derived macrophages (MDM) was significantly enhanced by PCV2. During monocyte-macrophage differentiation, the PCV2 antigen-containing rate and formation of multinucleated giant cells (MGC) were significantly increased in MDM when compared to those in Mo. The MDM-derived MGC displayed a significantly higher PCV2 antigen-containing rate than did the mono-nucleated MDM. Supernatants from PCV2-inoculated MDM at 24 h post-inoculation induced an increased tendency of chemotactic activity for blood Mo. At the same inoculation time period, levels of mRNA expression of the monocytic chemokines, monocyte chemoattractant protein-1 and macrophage inflammatory protein-1, also significantly increased in PCV2-inoculated MDM. The results suggest that PCV2 alone may induce cell proliferation, fusion, and chemokine expression in swine monocytic cells. Thus, PCV2 itself may play a significant role in the induction of granulomatous inflammation in PMWS-affected pigs.